2020
DOI: 10.1155/2020/6497408
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of a General Sextic Functional Equation by Fixed Point Theory

Abstract: In this paper, we will consider the generalized sextic functional equation ∑ i = 0 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Also, by fixed point theorem, Roh et al [24] showed the stability of the general sextic functional equation for the mapping f such that Df x, y ð Þ= 〠 7 i=0…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, by fixed point theorem, Roh et al [24] showed the stability of the general sextic functional equation for the mapping f such that Df x, y ð Þ= 〠 7 i=0…”
Section: Discussionmentioning
confidence: 99%
“…For a number of years now, many interesting results of the stability problems to several functional equations (or involving the range from additive functional equation to sextic functional equation) have been investigated; see, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the papers [16,[25][26][27][28][29][30][31][32][33], one can find hyperstability results for various types of functional equation. Recent results regarding the stability of the functional equation described in Equation (1) with n < 9 can be found in [34][35][36][37][38][39], and hyperstability results for this functional equation with n < 9 can be found in [38,40]. Note that the superstability of a functional equation requires that any mapping satisfying the equation approximately (in some sense) must be either a real solution to it or a bounded mapping, while hyperstability requires that any mapping satisfying the equation approximately (in some sense) must be a real solution to it.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the stability of a general quintic functional equation has been studied by S. S. Jin et al [24], and the stability of the general sextic function equation has been obtained by Y. H. Lee [25], I. S, Chang et al [26], and J. Roh et al [27].…”
Section: Introductionmentioning
confidence: 99%